Estrategias comunicacionales para contribuir a la reactivación del ferrocarril como aporte al desarrollo turístico en el cantón Riobamba, provincia Chimborazo, año 2022 - Carvajal Vaca, Anabel Wendy (2022)
The purpose of this research work was to design communication strategies to contribute to the reactivation of the railway as a contribution to tourism development in the Riobamba canton. Therefore, for the development of the research, the methodology with a mixed approach was applied, that is, qualitative and quantitative, in order to obtain true and exact information on the subject of study. Also, exploratory, descriptive and field research was applied in an integrated manner with deductive, inductive, analytical and bibliographic methods in order to describe each of the causes of the problem of the object of study. For the collection of information, interview techniques were applied to the authorities that are involved in the issue of the Riobamba Canton Railway, since they are the key actors for the development of the issue raised. In the same way, surveys were carried out on national and foreign tourists to have different opinions regarding the subject being studied. It should be noted that instruments such as secondary information, questionnaire and interview script were also used, which facilitated obtaining more detailed and concrete information. The responses of national and foreign tourists stated that they fully agree with the reactivation of the railway since it helps the economy, the tourism of the communities and the Riobamba canton. It is concluded that the design of communication strategies would contribute to the reactivation of the railway since it will help to market this tourist product more to have greater diffusion in the media and therefore the railway is known nationally and internationally. With the proposed proposal, a greater tourist demand for the railway will also be achieved and thus contribute to the economy of the canton, generating higher income margins for hotels, restaurants, travel agencies and entrepreneurs.